Employee Engagement as a Mediator between Employee Experience and Perceived Organizational Performance for Sustainable Airport Operations after the Covid-19 Crisis: A Multigroup Analysis - Vorapuksirikool, Voralux; Na Chiangmai, Chartchai (ASEAN Journal of Management & Innovation, 2024)
This study examines the mediating role of employee engagement on the relationship between employee experience and perceived organizational performance for sustainable airport operations after the COVID-19 crisis. Multigroup analysis was utilized to explore possible differences in this relationship between managers and employees. Stratified random sampling was used to select samples from six airports in Thailand. Data were collected via questionnaire from 552 participants, divided into 276 managers and 276 employees. A measurement invariance approach was implemented to verify that the measurement used in this study works the same for both groups. Multigroup structural equation modeling was applied to analyze the hypotheses. Results revealed that employee experience had a significantly positive and direct effect on organizational performance and employee engagement. However, employee engagement did not have significantly direct and indirect effects on organizational performance. Therefore, employee engagement did not perform as a mediator in this relationship. In addition, no significant differences were found between the groups of managers and employees under this relationship. These findings are noteworthy for airports to focus on employee experience across groups to redesign and continuously transform airports into sustainable airport operations after the COVID-19 crisis in the right direction.